Recurrent Urinary Bladder Paraganglioma - Ali A. Al-Zahrani (Advances in Urology)
A 39-year-old male presented with recurrent attacks of painless haematuria. The patient has a history of partial cystectomy for bladder paraganglioma 10 years prior to the presentation. Imaging study and cystoscopic examination revealed a small anterior wall bladder tumor. The histological examination of the lesion confirmed that it was a urinary paraganglioma. Partial cystectomy was performed to this recurrent lesion. This case report stresses the importance of life-long follow-up of these lesions.